Medidas estándar para el análisis morfométrico del riñón durante la regeneración en pez cebra (danio rerio) (2021)
The pathologies associated with kidney damage worldwide are on the increase, for this reason, it is necessary to find strategies that allow us to propose solutions for these problems. An approach that has gained strength in recent years is the study of kidney regeneration. However, very few quantitative approaches have been applied to study the progression of the regeneration after an induced lesion. Zebrafish is a model organism that allows us to study in detail the kidney regeneration processes. In this study, for the first time, standard parameters are established to address lesion progression, using the number of proximal tubule nuclei, and proximal tubules and its lumen area.